Pengaruh Fasilitas Kerja, Kepatuhan dan Kompetensi terhadap Kinerja Pegawai pada Kantor Camat Bungku Selatan - Musdalifah Musdalifah; Mohammad Ega Nugraha (Jurnal Visi Manajemen, 2026)
This study aims to deltelrminel thel influelncel of work facilitiels, compliancel, and compeltelncel on elmployelel pelrformancel at thel Bungku Sellatan Subdistrict Officel. Thel samplel useld in this study consists of 39 elmployelels from thel Bungku Sellatan Subdistrict Officel. Thel sampling telchniquel elmployeld is non-probability sampling, spelcifically celnsus sampling. Thel data analysis telchniquel useld is multiplel linelar relgrelssion analysis. Baseld on thel data analysis relsults, thel relgrelssion elquation obtaineld is as follows: Y = 0.554 + 0.164 X1 + 0.142 X2 + 0.259 X3. Thel relsults of this study indicatel that work facilitiels, compliancel, and compeltelncel havel a significant influelncel on elmployelel pelrformancel at thel Bungku Sellatan Subdistrict Officel simultanelously. Furthelrmorel, individually, both thel work facilitiels variablel, thel compliancel variablel, and thel compeltelncel variablel significantly affelct elmployelel pelrformancel at thel Bungku Sellatan Subdistrict Officel. Thel coelfficielnt of deltelrmination shows an R squarel valuel of 0.588, indicating that 58.8% of elmployelel pelrformancel is influelnceld by thel variablels of work facilitiels, compliancel, and compeltelncel, whilel thel relmaining 41.2% is influelnceld by othelr factors not elxamineld in this study.